Theoretical Prediction of Spinel Na2InxSc0.666−xCl4 and Rock‐Salt Na3In1−xScxCl6 Superionic Conductors for All‐Solid‐State Sodium‐Ion Batteries. Issue 1 (11th November 2022) - Hussain, Fiaz; Yu, Pengcheng; Zhu, Jinlong; Xia, Hui; Zhao, Yusheng; Xia, Wei
Abstract: The demand for green, clean, and low‐cost energy based on next generation all‐solid‐state batteries is increasing day by day. Compared with all‐solid‐state lithium‐ion batteries, all‐solid‐state sodium‐ion batteries (ASSSIBs) feature better environmental credentials, higher safety, and higher earth abundance. To develop such type of battery system, efficient solid‐state sodium electrolytes with high ionic conductivity at room temperature, wide electrochemical stability window, low electronic conductivity, and interface compatibility are needed, but are rarely reported. In this article, density functional theory and ab initio molecular dynamic simulations are performed to predict new sodium solid electrolytes, which produces a series of sodium superionic conductors with remarkable ion‐conducting properties and interface compatibility. The optimized composition discovered in this work can afford an extraordinary Na‐ionic conductivity of up to 8 mS cm −1 with an extremely low activation energy of 0.20 eV; in addition to the high chemical and electrochemical stabilities, which could be a central idea for the experimental study and accelerate the development of high‐performance ASSSIBs. Abstract : All‐solid‐state sodium‐ion batteries (ASSSIB) are considered as a promising alternative to traditional lithium‐ion batteries for large‐scale energy storage systems and electric vehicles. In this work, comprehensive theoretical investigations are performed to accelerate the development of advanced solid electrolytes as the core materials of ASSSIB.